Midwife-assisted management of obstructed labour during second-stage caesarean section using the Patwardhan technique: a case report - Ramar, Bagavathi K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Obstructed labour is a preventable yet life‑threatening obstetric emergency that contributes substantially to maternal and perinatal morbidity and mortality, particularly in low‑ and middle‑income countries. Early identification and timely intervention are critical to improving outcomes. Midwives frequently serve as first responders during labour and play a pivotal role in recognizing deviations from normal progress, initiating emergency measures, and coordinating multidisciplinary care. To describe the successful midwife-assisted management of obstructed labour during a second-stage caesarean section using the Patwardhan technique. This case report describes the management of a primigravida woman with second‑stage obstructed labour and foetal distress, in whom prompt midwifery assessment using the partograph and rapid escalation of care resulted in an emergency caesarean section performed with the Patwardhan technique. Favourable maternal and neonatal outcomes highlight the essential role of midwives as frontline guardians in obstetric emergencies.